Persons and Immortality - Bryson, Kenneth A., (Value Inquiry Book Series ;, 1999)
The religious belief in personal immortality depends on the evidence for the existence of God, an immaterial soul or mind, and human nature. We also need to support the view that God will always want to maintain relationships with us in the afterlife. So, immortality is a hard sell. The suffering of innocent victims suggests that the existence of a loving God is not self-evident. Furthermore, the soul's separation from the body at death raises the troublesome problem of personal identity. How can that be me in the afterlife without my body? The tradition from Plato to Descartes plants the seed of personal immortality in our rational nature. But the deconstruction of human nature suggests that our species is not special. Yet, the belief in immortality lingers. The first step in the reconstruction of personal immortality is found in systems theory, or belief that the whole individuates the part. This view suggests that we are the outcome of relationships rather than eternal natures entering into relationships. We are the product of relationships taking place at three basic levels. 1. In psyche where being human is the result of a tendency toward good and evil. 2. As social entities where the existence of other human beings individuates us. 3. In being's unconcealment where the intelligibility of things provides a foundation for epistemic life. Heidegger's view of the nothing or horizon surrounding being allows us to identify God as creator entering into personal relationships with us - a view supported by contemporary science. That will be me in the afterlife, if the relationships that individuate me in my pre-mortem state continue into my post-mortem existence. The reversal in being's unconcealment suggests that human death continues the cycle of personal existence.